Penerapan Latihan Drill untuk Meningkatkan Kemampuan Passing pada Ekstrakulikuler Futsal - Ramadhan, Haris; Prananosa, Ahmad Gawdy; Atmanegara, Doni (e-SPORT: Jurnal Pendidikan Jasmani, Kesehatan dan Rekreasi, 2025)
This study aims to determine the effectiveness of drill training in improving passing ability in the futsal extracurricular activity at SMA Negeri 5 Lubuklinggau. The study was conducted from May 2 to June 2, 2025. The research method employed was a descriptive, quantitative approach, utilizing an experimental design with a one-group pretest-posttest design. The results showed a significant difference in passing ability using drill training in the futsal extracurricular activity at SMA Negeri 5 Lubuklinggau City. The results of the significance test between the pretest and posttest showed a t-test value of 24.004, df = 14, and a significance level of 0.05, indicating a statistically significant difference between the pretest and posttest scores. The conclusion is that drill training can improve passing ability in the futsal extracurricular activity at SMA Negeri 5 Lubuklinggau City.   Keywords: Futsal, Drill Training, Passing